Moving Workers Historical Perspectives on Labour, Coercion and Im/Mobilities - Vilhelmsson, Vilhelm; Bernardi, Claudia; Müller, Viola Franziska; Stojić, Biljana (Work in Global and Historical Perspective, 2023)
This book brings together a variety of regions and periods to provide fresh perspectives on the study of labour. It deconstructs the polarisation between mobility and immobilisation in labour history and instead stresses their close entanglement with each other. Following interactive processes of control and resistance, this book makes a compelling case for the historically intertwined trajectories of labour im/mobility and labour coercion.